ANALYSIS OF PROFIT GROWTH, PROFITABILITY, CAPITAL STRUCTURE, LIQUIDITY AND COMPANY SIZE OF PROFIT QUALITY - Mohamad Zulman Hakim; Yuyun Naelufar (Jurnal Akademi Akuntansi, 2020)
The purpose of this study is to examine the effect of earnings growth, profitability, capital structure, liquidity and company size on earnings quality in companies of Basic and Chemical Industries Listed on the Indonesia Stock Exchange (IDX). The time period of the study is 5 years, namely the 2014-2018 period.The population in this study includes all basic and chemical industry companies listed on the Indonesia Stock Exchange. The sampling technique uses purposive sampling technique. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analytical method used is panel data regression analysis.The results of the study simultaneously showed that the independent variable affected earnings quality. While partially, company size, profitability, liquidity and company size variables have no effect on earnings quality, but capital structure variables that are proxy by leverage have a positive effect on earnings quality.